Corporate Citizenship and Employee Outcomes: Does a High-Commitment Work System Matter? - Lin, Yi-Ting (Journal of business ethics, 2019)
Interest in corporate citizenship (CC) has been burgeoning in the academic and managerial realms for decades. While a psychological CC climate has been conceptualized and has received empirical support for its relationship with employee outcomes, the organizational climate perspective of CC has not yet been explored. In the present study, we develop and examine a mediated moderation model that elaborates the underlying psychological process and the contingency of organizational CC climate and its individual outcomes. We follow 539 employees in 26 firms for approximately one year in Taiwan. We find that organizational CC climate is positively related to employees’ organizational identification (OI) and that the firm’s high-commitment work system (HCWS) can augment the effect of CC on employees’ OI. In addition, employees’ OI plays a psychological process role in mediating the interactive effect of the firm’s CC and HCWS on employees’ workplace outcomes, including their job satisfaction (JS) and turnover intention. The findings shed light on the alignment of CC and human resource functions and argue that the Confucian Asian context may act as a stepping stone for the impact of CC on employees’ attitudes. The study offers valuable implications for both researchers and practitioners.